Unilateral emission reductions when there are cross-country technology spillovers - Rolf Golombek; Michael Hoel (University of Oslo, Department of Economics, 2004)
With limited participation in an international climate agreement, standard economic analysis suggests that a unilateral action taken by a group of countries in order to reduce its emissions is likely to be undermined by increases in emissions from other countries (carbon leakage). While analyses of carbon leakage typically have regarded the technology in each country as given, abatement technologies are endogenous, and thus technology development may be affected by environmental policies. We demonstrate that with endogenous technologies and technology diffusion between countries, it is no longer obvious that reduced emissions in some countries will increase emissions in other countries. We identify cases in which reduced emissions in some countries might reduce emissions also in other countries.
Keywords: O30; Q54; 330; transboundary pollution; unilateral environmental action; R&D expenditures; technology spillovers; Umweltschutz; Grenzüberschreitende Umweltbelastung; Spillover-Effekt